THE ROLE AND RELEVANCE OF SPORTS PSYCHOLOGY IN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Psychology is the scientific study of behavior. It is the science of the mind and soul. Earlier, Human Psychology was thought or meant the reading of peoples mind. However, psychology is far from mindreading only psychology is presently seen as the science of human behavior, his experiences and activities. Sport psychology has many definitions, with many systems and methods offered by many practitioners. Some see it as positive thinking while others use techniques such as visualization and imagery to try to cause positive outcomes. Sport psychology is an interdisciplinary science that draws on knowledge from the field of kinesiology and psychology. It involves the study of how psychological factors affect performance and how participation in sports and exercise affect psychological and physical factors. In addition to instruction and training of psychological skills for performance improvement, applied sport psychology may include work with athletes, coaches, and parent regarding injury, rehabilitation, communication, team building, and career transition, conclusion and recommendations were made on the way forward to athletes such that athletes during training sessions or competition should take only the prescribed drugs dose by physicians and medical doctors.
Keywords: Psychology, Sport, Relevance, Role.